Implementation of Smart Lectures for Chemistry Teachers of the MGMP in Padang Panjang City - Rahadian Zainul; Budhi Oktavia; Dony Novaliendry; Amalia Putri Lubis (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2022)
The Chemistry Teachers Working Group (MGMP) of Padang Panjang City serves as a forum for senior high school chemistry teachers in Padang Panjang to collaboratively develop their professional careers and scientific competencies. The teachers' enthusiasm to improve more effective, high-quality, and innovative learning was demonstrated through their request for training in designing and implementing E-Learning in senior high school chemistry instruction. The methods used in the introduction and development program related to E-Learning through the flagship product, Smart Lecture, were conducted through lectures, question-and-answer sessions, mentoring, and workshops. The results of the community service program showed that: (1) the training participants were able to understand the preparation, design, and implementation of high-quality and interactive E-Learning in senior high school chemistry instruction, thereby improving the quality of chemistry learning; (2) the chemistry teachers of the MGMP of Padang Panjang City were able to motivate other teachers to diversify the strategies used in senior high school chemistry instruction; and (3) chemistry teachers were able to apply and implement senior high school chemistry learning strategies using E-Learning.